Growth and yield of bari mung-5 (Vigna radiata L. Wilczek) following TIBA application (Dhaka University Journal of Biological Sciences, 2014)
An experiment was conducted to evaluate the effect of TIBA (0, 20, 50, 100, 150 mg/l) on the growth and yield attributes of BARI Mung?5 laid out in RBD. Plant height decreased due to TIBA treatments. Number of branches and leaves per plant were found to increase in all the treatments at all the ages of growth except at 7 DAS and the maximum number of branches and leaves were recorded due to 20 mg/l TIBA treatment. Dry matter per plant increased due to 20 mg/l TIBA in most cases and was significantly highest at harvest. All the yield contributing characters showed positive response to 20 mg/l TIBA treatment. Number of pods and seeds per plant and fresh and dry weights of pods significantly differed from all other treatments. Increase in yield per plant and yield per hectare following 20 mg/l TIBA was 22.60 and 22.80% over the control, respectively. The highest harvest index was also recorded from 20 mg/l TIBA followed by control. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20098 Dhaka Univ. J. Biol. Sci. 23(2): 179-185, 2014